Biomechanical testing of different posterior fusion devices on lumbar spinal range of motion. (February 2019) - Hartmann, Frank; Nusselt, Thomas; Maier, Gerrit; Rommens, Pol Maria; Gercek, Erol
Abstract: Background: Recent minimal-invasive posterior fusion devices are supposed to provide stability and obtain fusion in combination with interbody cages in the instrumented segment. The aim of the present study is to evaluate the primary stability of two minimal-invasive posterior prototypes compared to an established spinous process plate and standard pedicle screw instrumentation. Methods: Seven fresh frozen human cadaver lumbar spines (L2–L5) were tested in a spinal testing device with a moment of 7.5 Nm. Spinal stability was determined as mean range of motion (RoM) in the segment L3/L4 during extension-flexion, lateral bending and axial rotation. The RoM was measured during five conditions: 1. intact; 2. working prototype composed of an interspinous device and process plates; 3. an established spinous process fixation device 4. working prototype of facet fixation and 5. pedicle screw fixation. Findings: All devices caused a significant reduction of RoM during extension-flexion. The RoM during lateral bending was significantly reduced to 37% (of intact) by pedicle screws and 68% by facet fixation prototype. During axial rotation the RoM was significantly reduced to 52% by pedicle screws and to 86% by facet fixation prototype. The other devices had no significant influence on RoM during lateral bending and axial rotation. Interpretation: The facet fixation prototype provided less primary stability compared to pedicle screws, but had significant advantages over spinous process fixation techniques. The results encourage further testing of this implant as a minimal-invasive approach for posterior fixation. Highlights: Spinous process fixation lacks stability during lateral bending and axial rotation. Spinous process fixation requires additional interbody or posterior fixation. Facet fixation provides higher stability, but is inferior to pedicle screws. Facet fixation is a promising minimal-invasive approach for posterior fixation.